Artificial Intellect in Economics and System of Economic Security - I. A. Sushkova; L. N. Mamaeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The national program ‘Digital Economy of the Russian Federation’ was elaborated by the decree of the President of the Russian Federation dated May 7, 2018 and now it is being implemented in 10 principle lines. For instance, possibilities to use artificial intellect to provide sustainable economic development and economic security of business entities and state as a whole are analyzed. The necessity to introduce artificial intellect in the system of risk management at business entities is studied. Changes in the volume of Russian and overseas markets in artificial intellect technologies are estimated. It is underlined that the foundation of developing national economy in current circumstances and providing the adequate level of economic security are formed by transition to neo-industrial model of economy development. In fact, competitive advantages can be obtained by economy, which allows the maximum use of innovation technologies. The authors identify problems hindering the development of artificial intellect technologies in Russia, which can be overcome only on the basis of complex and systematic approach. They point out that artificial intellect technologies can be used in different fields of business entities’ work, as they can eliminate the majority of the so-called system conflicts and contradictions at the expense of specific individual resources.